Terrorism in Years 2015-2022. Selected Global and Regional Trends - Stempień, Marta (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2023)
In 2019, terrorism-related deaths decreased for the fifth consecutive year (by 15.5 %). However, the decline in the number of victims does not mean that there are no new, disturbing trends in the international system. Though, it is not easy to grasp the phenomenon of terrorism in the regions where asymmetric security threats coexist. Often, local armed conflicts and violence interlock terrorist actions. The following article has the form of a comparative study. The research goal is to identify trends taking place in the international and regional space related to the phenomenon of terrorism in years 2015-2022. The objects of research are the states most impacted by terrorism and selected states of the regional security complexes perceived as systems. Research has shown that the phenomenon of terrorism in the years 2015-2022 was associated with instability and conflict.